The gnd gene of Buchnera as a new, effective DNA barcode for aphid identification. (12th May 2013) - CHEN, RUI; JIANG, LI‐YUN; LIU, LIN; LIU, QING‐HUA; WEN, JUAN; ZHANG, RUI‐LING; LI, XING‐YI; WANG, YUAN; LEI, FU‐MIN; QIAO, GE‐XIA
Abstract DNA barcoding uses a standard DNA sequence to facilitate species identification. Although the COI gene has been adopted as the standard, COI alone is imperfect due to several shortcomings. The primary endosymbiont of aphids, Buchnera, has higher evolutionary rates and interspecies divergence than its co‐diverging aphid hosts, making it a potential tool for resolving the ambiguities in aphid taxonomy. We compared the effectiveness of employing two different DNA regions, gnd and COI, for the discrimination of over 100 species of aphids. The mean interspecific divergence of the gnd region was significantly higher than the mean intraspecific variation; there were nearly nonoverlapping distributions between the intra‐ and interspecific samples. In contrast, COI showed a lower interspecific divergence, which led to difficulties in identifying closely related species. Our results show that gnd can identify species in the Aphididae, which suggests that the gnd region of Buchnera is a potentially effective barcode for aphid species identification. We also recommend the 2‐locus combination of gnd + COI as the aphid barcode. This will provide a universal framework for the routine use of DNA sequence data to identify specimens and contribute toward the discovery of overlooked species of aphids.